Sarcoid pleural effusion: three cases and review of the literature. Issue 4 (April 1980) - Nicholls, A J; Friend, J A; Legge, J S
Abstract : Pleural sarcoidosis is rare--it is little recognised in Birtian although several cases have been reported in the international literature. Three white men with pleural effusions caused by sacroidosis have been seen in a two-year period when approximately 60 new cases of thoracic sarcoidosis have been presented. In one patient a recurrent massive effusion was only diagnosed as being caused by sarcoidosis after thoractomy, and in two further patients small symptomatic pleural effusions were present at the onset of typical sarcoidosis. Two patients were successfully treated with steroids and the third improved spontaneously. Percutaneous biopsy is not always helpful in diagnosing pleural sarcoidosis, but a lymphocytic, often blood-stained, pleural aspirate is highly characteristic. While other diseases may coexist, a pleural effusion in a patient with histologically proven sarcoidosis is more likely to be caused by the primary disease than by any other condition.